2008
DOI: 10.1002/mus.21060
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term intensive electrically stimulated cycling by spinal cord–injured people: Effect on muscle properties and their relation to power output

Abstract: Inactivity and muscular adaptations following spinal cord injury (SCI) result in secondary complications such as cardiovascular disease, obesity, and pressure sores. Functional electrically stimulated (FES) cycling can potentially reduce these complications, but previous studies have provided inconsistent results. We studied the effect of intensive long-term FES cycle training on muscle properties in 11 SCI subjects (mean +/- SEM: 41.8 +/- 2.3 years) who had trained for up to 1 hour/day, 5 days/week, for 1 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 39 publications
2
56
0
1
Order By: Relevance
“…13,14 In a randomized controlled trial by Johnston et al 15 of pediatric SCI cases, an increase was seen in quadriceps strength with 6 months of FES exercise in comparison with passive cycling and non-cycling electrical stimulation and an increase in quadriceps muscle volume was determined with both FES and noncycling electrical stimulation. Duffel et al 16 reported improvements in quadriceps torque and power output with a 1-year FES cycling exercise program in patients with SCI. In addition to studies assessing the effect of FES cycling on muscle in a laboratory setting, the clinical relevance of this gain in muscle strength and size by FES has also been evaluated by clinical outcomes reflecting functional improvement in SCI.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 In a randomized controlled trial by Johnston et al 15 of pediatric SCI cases, an increase was seen in quadriceps strength with 6 months of FES exercise in comparison with passive cycling and non-cycling electrical stimulation and an increase in quadriceps muscle volume was determined with both FES and noncycling electrical stimulation. Duffel et al 16 reported improvements in quadriceps torque and power output with a 1-year FES cycling exercise program in patients with SCI. In addition to studies assessing the effect of FES cycling on muscle in a laboratory setting, the clinical relevance of this gain in muscle strength and size by FES has also been evaluated by clinical outcomes reflecting functional improvement in SCI.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies prescribed exercise 3 Â per week for 6-12 weeks, although two studies showed particularly large improvements in lower limb power output following 1 year of FES cycling, 3-5 Â per week. 20,21 Unfortunately, it is difficult to pinpoint the exercise intensity required for improvements because the majority of studies (11 of 16) employed FES exercise; stimulation parameters vary widely among these studies and progression typically occurs as individually tolerated. However, moderate-intensity arm ergometry exercise (70-80% max HR or 50% HR reserve) combined with resistance training (progressed to repetitions with 70-80% of the one repetition maximum) seems sufficient for long-term improvements.…”
Section: Standingmentioning
confidence: 99%
“…used extensively over several decades as an effective means to reduce or reverse muscle atrophy and to obtain some functional recovery by rehabilitation strategies for spinal cord injury patients, [1][2][3][4][5] including those paraplegics with permanent and complete denervation of the legs (complete Conus and Cauda Equina Syndrome). [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The benefits of this technology are being expanded into other areas, and FES has been recently utilized for injury rehabilitation and performance enhancement in horses.…”
Section: Functional Electrical Stimulation (Fes) Has Beenmentioning
confidence: 99%